Building codes illustrated a guide to understanding the 2015 international building code® - Ching, Francis D. K. 1943-; Winkel, Steven R. (John Wiley & Sons, Inc., 2016)
Building Codes Illustrated: A Guide to the 2015 International Building Code, Fifth Edition is a bestselling complement to the International Building Code, or IBC. Designed to give you an insider's look at the origins of the IBC, how it can be interpreted, and how it applies to design and construction, this updated text offers new information regarding hazmat occupancies, hospitals, and nursing homes, major changes to how building heights and areas are presented, as well as means of egress, and the latest information on building materials, interior environments, and structural provisions. Francis D.K. Ching's distinctive illustrations and the code expertise of Steven Winkel, FAIA, give students and professionals in architecture, interior design, construction, and engineering industries a user-friendly, easy-to-use guide to fundamentally understanding the 2015 IBC.